Planning Annual Training for Runners Running Over Obstacles - Z.B.Khamraeva (Genius Publishing Group, 2022)
This article focuses on the accuracy of the loads given to athletes and the perfect study of the technique of running over obstacles when planning the annual training of runners over hurdles. The article analyzes the scientific literature and research.
Keywords: excellent; speed; methodological; literature